2015
DOI: 10.3892/mmr.2015.3954
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone morphogenetic protein-2 in osteogenic differentiation of mesenchymal stem cells

Abstract: Bone mesenchymal stem cells (BMSCs) have been an area of interest in biomedical research and tissue engineering due to their diverse differentiation abilities. In osteogenesis, bone morphogenetic proteins (BMPs), particularly BMP-2, are important. However, the effect of BMP-2 on the osteogenetic capacity of BMSCs remains to be fully elucidated. In the present study, primary rat BMSCs were infected with a recombinant lentivirus carrying the BMP-2 gene (Lenti-BMP-2), and the effects of BMP-2 on the activity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 29 publications
6
70
0
Order By: Relevance
“…The present study demon-demonstrated that, like osteoblasts derived from human mesenchymal stem cells (46,47), OM-treated PDMCs expressed BMP-2. BMPs are known to stimulate new bone formation (48).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The present study demon-demonstrated that, like osteoblasts derived from human mesenchymal stem cells (46,47), OM-treated PDMCs expressed BMP-2. BMPs are known to stimulate new bone formation (48).…”
Section: Discussionsupporting
confidence: 53%
“…BMPs are known to stimulate new bone formation (48). Sun et al (46) revealed that BMP-2 may improve bone healing in an animal model. Furthermore, the molecules RUNX2 and ALP, which are associated with osteoblast differentiation and bone activity, were also upregulated during the initial stages of differentiation (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…While the influence of BMP-2 on BMSC differentiation has been studied extensively in 2D monolayers (Sun et al 2015), its effect on 3D microtissue cultures has been less well explored. As undifferentiated BMSC organised into 3D microtissues behave differently than those cultured in 2D monolayers (Wang et al 2009;Frith et al 2010;Kabiri et al 2012), we chose to characterise BMSC osteogenic induction in 3D microtissue cultures.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…For instance, in osteogenesis, these are generally ascorbate, b-glycerophosphate, and bone morphogenetic proteins (BMPs), or dexamethasone (DEX) (Cook and Genever, 2013). BMPs such as BMP-2 stimulate the expression of major osteogenic genes such as osteopontin, osteocalcin and Runx2 (Runt-related transcription factor 2) (Sun et al, 2015). Adipogenesis requires DEX, isobutylmethylxanthine, indomethacin, and insulin (Cook and Genever, 2013).…”
Section: Soluble Factors In Mediamentioning
confidence: 99%